Análise do perfil etio-epidemiológico e suscetibilidade microbiana de pacientes idosos com infecção urinária (Research, Society and Development, 2023)
Introduction: Urinary tract infection (UTI) is a very prevalent disease in Brazil. The elderly are considered a risk group due to the anatomical and physiological changes and comorbidities found with advancing age. Objectives: Investigate the epidemiological profile and susceptibility of antibiotics in urinary tract infections in the elderly. Methodology: Descriptive, observational and cross-sectional study of the analysis of etiological agents and their antimicrobial susceptibility profile according to epidemiological characteristics during the period from 2018 to July 2021. Urine cultures were collected and attached to the Microsoft Excel program and the Epi info 7.0 software used for organization and analysis of statistics. Fisher's chi-square test and odds ratio were chosen for data evaluation. Results: 7960 urine cultures were analyzed, of which 2050 were positive urine cultures. Women had a higher positivity rate among the age group of 60 to 69 years. The most prevalent uropathogen was Escherichia coli, followed by Enterococcus spp and Enterobacter spp. Among patients positive for Escherichia coli, the lowest rates of antimicrobial resistance were: Ceftazidime, Ceftriaxone, Amoxicillin + Clavulanate, Fosfomycin, Nitrofurantoin and Imipenem and higher rates of resistance to Ampicillin, Aztreonam, Cefepime, Ciprofloxacin, Levofloxacin and Norfloxacin. Conclusion: Escherichia coli was more prevalent, affecting mainly women between 60 and 69 years old. Men had higher rates of antimicrobial resistance, with an increase in this rate with age. Susceptibility rates varied according to epidemiological aspects of the patient. To choose the antibiotic it is necessary to consider the clinical individuality of the patient.